Educational Attainment: Analysis by Immigrant Generation - Barry R. Chiswick; Noyna DebBurman (Institute for the Study of Labor (IZA), 2003)
This paper presents a theoretical and empirical analysis of the largely ignored issue of the determinants of the educational attainment of adults by immigrant generation. Using Current Population Survey (CPS) data, differences in educational attainment are analyzed by immigrant generation (first, second, and higher order generations), and among the foreign born by country of birth and age at immigration. Second-generation American adults have the highest level of schooling, exceeding that of the foreign born and of the native born with native-born parents. Teenage immigration is associated with fewer years of schooling compared to those who immigrated at pre-teen or post-teen ages. The gender difference in educational attainment is greatest among the foreign born. Hispanics and Blacks lag behind the non-Hispanic whites in their educational attainment, with the gap narrowing for higher order immigrant generations among Hispanics, but rising among blacks.
Keywords: J61; I21; J24; 330; demand for schooling; human capital; immigrants second generation; Bildungsniveau; Migranten; Einwanderung; Bildungsverhalten; Generationenbeziehungen; Schätzung; Vereinigte Staaten